Lucas, Keynes, and the crisis - David Laidler (The University of Western Ontario, Department of Economics, 2009)
This paper examines Robert E. Lucas's views on the relationship of macroeconomics to real world economic phenomena, and on Keynes's place in its history, suggesting that these stem from a particular and debatable understanding of how the subdiscipline has evolved. It considers some implications for today's awkward economic facts of aspects of Keynes' General Theory, not so much its speculations about the role of psychology and social conventions in the economic decisions of individual agents recently highlighted by Akerlof and Shiller (2009) however, as its insights into the influence of the monetary system on the coordination of these decisions, along lines later extended by Clower (1965) and Leijonhufvud (1968). It concludes that the questions about co-ordination that Keynes addressed, not to mention some of his answers, are well worth revisiting.
Keywords: B22; B31; E12; E13; E32; 330; Crisis; Co-ordination; Clearing Markets; Auctioneer; Money; Financial Markets; Animal Spirits; Psychology; Keynes; Lucas; Dogmengeschichte; Keynesianismus; Makroökonomik; Theorie